The Influence of the Toddler Mother Class on Increasing Knowledge of Stimulation of Toddler Development at the Kanda Health Center - Wardhani, Yeni; Romauli, Suryati (Journal of Midwifery and Nursing, 2024)
Age 0-5 years is the golden age where children need to pay attention to growth and development. The optimal growth and development of toddlers depends on how active the role of the family, especially parents, in stimulating the development of toddlers. Mothers who provide optimal early stimulation, will significantly affect the child's motor development. Health workers also play a role in monitoring the development of toddlers by running an integrated posyandu program by activating family development activities and providing IEC to parents to stimulate the development of their toddlers, namely with classes for mothers of toddlers. This study aims to determine the influence of the toddler mother class on increasing knowledge of stimulation of toddler development aged 1-5 years at the Kanda Health Center, Jayapura Regency. This type of research is quasi-experimental with a pretest posttest design with control group. The sample used was 32 respondents with probability sampling techniques. Statistical test using independent sample t-test. The results showed that there was an influence of the toddler mother class on increasing knowledge of developmental stimulation of toddlers aged 1-5 years at the Kanda Health Center with a p-value of 0.001 < 0.05.  The conclusion of this study showed that there was a difference in knowledge of mothers of toddlers before and after the class of mothers of toddlers with an average of 49.64 to 92.27. This study suggests that health workers and mothers of toddlers take an active part in classes to monitor the development of toddlers